Law Enforcement Against Online Prostitution Crimes Through the MiChat Application: Study of Decision Number 129/Pid.Sus/2021/PN KPH - Nixxon Rian P. Siahaan; Sriono Sriono; Wahyu Simon Tampubolon (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Kepahiang District Court Decision Number 129/Pid.Sus/2021/PN Kph analyzed the application of electronic evidence in the investigation of online prostitution through the MiChat application by the Kepahiang Police. Defendants Sanelia Amelia and Monicxa Caroline were proven to have violated Article 45 paragraph (1) in conjunction with Article 27 paragraph (1) of Law No. 19 of 2016 concerning ITE in conjunction with Article 55 paragraph (1)¹ of the Criminal Code, with a prison sentence of 1 year and 3 months each. The main evidence includes the MiChat status (